2020
DOI: 10.1016/j.envint.2020.105537
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation and laboratory confirmed acute respiratory infection (ARI) rates in college residence halls in College Park, Maryland

Abstract: A B S T R A C TStrategies to protect building occupants from the risk of acute respiratory infection (ARI) need to consider ventilation for its ability to dilute and remove indoor bioaerosols. Prior studies have described an association of increased self-reported colds and influenza-like symptoms with low ventilation but have not combined rigorous characterization of ventilation with assessment of laboratory confirmed infections. We report a study designed to fill this gap. We followed laboratory confirmed ARI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 37 publications
4
48
0
1
Order By: Relevance
“…In such well-mixed spaces, one is no safer from airborne pathogens at 60 feet than 6 feet. The Wells-Riley model 11,12 highlights the role of the room's ventilation outflow rate Q on the rate of infection, showing that the transmission rate is inversely proportional to Q, a trend supported by data on the spreading of airborne respiratory diseases on college campuses 34 . The additional effects of viral deactivation, sedimentation dynamics and the polydispersity of the suspended droplets were introduced by Stilianakis & Drossinos 13 and recently applied to COVID-19 18 .…”
mentioning
confidence: 85%
“…In such well-mixed spaces, one is no safer from airborne pathogens at 60 feet than 6 feet. The Wells-Riley model 11,12 highlights the role of the room's ventilation outflow rate Q on the rate of infection, showing that the transmission rate is inversely proportional to Q, a trend supported by data on the spreading of airborne respiratory diseases on college campuses 34 . The additional effects of viral deactivation, sedimentation dynamics and the polydispersity of the suspended droplets were introduced by Stilianakis & Drossinos 13 and recently applied to COVID-19 18 .…”
mentioning
confidence: 85%
“…ventilated dormitory, each with one infected and one susceptible roommate, given measured airborne viral shedding rates and modeled dormitory room ventilation of 12.1 (1 ACH) and 4.0 L/s (0.3 ACH) in a high and low ventilated dormitory, respectively, based on an analysis of indoor air ventilation (Appendix S5) 26. Reanalyzing the fine aerosol shedding rate for the 142 influenza cases using the final adjusted model from Yan et al4 gives median 5.8E + 6, 1.2E + 6, and 5.4E + 5 for days post onset 1, 2, and 3, respectively.…”
mentioning
confidence: 99%
“…12 The pre-COVID-19 naïve blood sera were collected in the context of a larger study to identifying acute respiratory infection (ARI) cases in a college resident community in the Eastern United States monitored using questionnaires and RT-qPCR. 28 From among de-identified blood specimens for which future research use authorization was obtained, five specimens that showed high IgG reactivity against human coronaviruses in the larger study were chosen for validation of the coronavirus antigen microarray. 13…”
Section: Specimen Collectionmentioning
confidence: 99%